Numerical simulation of three-dimensional hydrodynamic characteristics and pollutant diffusion behavior by ROMS model - Jing Ren (IWA Publishing, 2021)
Based on the ROMS (Regional Ocean Modeling System) model, a three-dimensional hydrodynamic model and a convection diffusion model are built in this paper. The three-dimensional tidal current model is intended to reflect the distribution characteristics of the tidal level and the flow field of water with different depths of the Bohai Bay. On this basis, a water exchange correlation matrix is adopted to analyze the water exchange characteristics of the offshore area of Binzhou City in the offshore planning functional area of Bohai Bay. Considering the functional planning of the offshore area of Binzhou city, the paper simulates how COD and NH4+-N in the water discharged from the sewage outfall of the city migrate and disperse under tidal current. In this way, the paper concludes the concentration distribution patterns of pollutants at different times. The results serve as basis and reference to delimitation of environmental management and control unit demarcation in Binzhou nearshore. HIGHLIGHTS Establish 3D hydrodynamic model of Bohai Bay.; Establish water exchange correlation matrix to analyze nearshore water transport characteristics.; Quantify the contribution of water exchange.; Effects of river pollution load on nearshore water quality were simulated by our hydrodynamic model.; Results serve as basis in delimitation of environmental management and control zone demarcation.;